2019
DOI: 10.7759/cureus.5198
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole-induced Vasculitis in a Hepatitis C Patient: A General Medicine Ward Perspective on Diagnosis and Management

Abstract: Purpura in hepatitis C patients has a wide range of possible etiologies, some of which include mixed cryoglobulinemia and idiopathic thrombocytopenic purpura. Levamisole is a common chemical used as a lacing agent for cocaine. It is believed to enhance the addictive properties of cocaine, but it has been associated with a vasculitis syndrome that most commonly presents with purpura and leukopenia. We report a case of a patient with hepatitis C and cocaine abuse who presented with vasculitis, thrombocytopenia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Numerous studies have observed that cessation of cocaine use leads to complete resolution of the condition [ 3 , 23–25 ]. Furthermore, where immunosuppressive therapies, such as CSs or CYC, were used (mainly in cases of renal involvement), full resolution was not achieved unless the patient stopped using cocaine [ 25 , 27 ]. In patients who did not stop using cocaine, resolution was never achieved [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have observed that cessation of cocaine use leads to complete resolution of the condition [ 3 , 23–25 ]. Furthermore, where immunosuppressive therapies, such as CSs or CYC, were used (mainly in cases of renal involvement), full resolution was not achieved unless the patient stopped using cocaine [ 25 , 27 ]. In patients who did not stop using cocaine, resolution was never achieved [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%